1990
DOI: 10.1111/j.1600-0676.1990.tb00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of a numerical scoring system for assessment of histological outcome in patients with chronic posttransfusion non‐A, non‐B hepatitis with or without antibodies to hepatitis C

Abstract: Abstract— A numerical scoring system was applied and compared to the conventional histological classification to assess the histological status of liver specimens from 37 patients with chronic posttransfusion non‐A, non‐B hepatitis followed for 7 to 105 months (mean 35 months). Four histological categories of alterations were assessed and scored: piecemeal necrosis (PMN), fibrosis and cirrhosis, lobular necrosis and portal inflammation. Sequential liver biopsies were obtained from 19 patients. PMN was generall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The aim of this study was to determine whether there was a correlation between genotype and the characteristic histological features that have been noted in hepatitis C infection. We also compared the sensitivity of the Knodell scoring system, which has been widely used (31), with two newer systems, the Scheuer and modified histological activity index (HAI), in detecting these histological differences. The application of numerical scoring systems has partly overcome discrepancies caused by intra-observer variation (8), and allow more subtle changes to be recorded compared to descriptive terms such as chronic persistent hepatitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this study was to determine whether there was a correlation between genotype and the characteristic histological features that have been noted in hepatitis C infection. We also compared the sensitivity of the Knodell scoring system, which has been widely used (31), with two newer systems, the Scheuer and modified histological activity index (HAI), in detecting these histological differences. The application of numerical scoring systems has partly overcome discrepancies caused by intra-observer variation (8), and allow more subtle changes to be recorded compared to descriptive terms such as chronic persistent hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of lobular inflammationidegeneration, the scores for the different systems are based on quite different definitions, as discussed in detail in the original papers. Briefly the Scheuer system scores inflammation, focal necrosis and bridging necrosis in this In one study, the Knodell system was applied to score the histological appearances of liver biopsies, from patients with non-A, non-B hepatitis (31). In patients with sequential biopsies, the severity of the scores for piecemeal necrosis were shown to correlate with progressing fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with chronic PTH-NANB have a marked tendency to progress slowly to cirrhosis, although they are often asymptomatic in the early stages of their disease (2). Histological signs of PMN have been shown to predict a later development of fibrosis/cirrhosis in both chronic hepatitis B (1 1) and chronic PTH-NANB (10). However, PMN in liver specimens from patients with chronic PTH-NANB is much less extensive (10) than in patients with chronic replicating hepatitis B (1 I).…”
Section: Discussionmentioning
confidence: 99%
“…The semi-quantitative histological scoring system described by Knodell et al (1 6) blindly applied to sequential liver biopsies has been found useful for the study of the outcome of chronic non-A non-B hepatitis (9), and for the assessment of the effect of interferon therapy on liver damage (12)(13)(14). Treatment with interferon improved all histological parameters, except fibrosis.…”
Section: Biochemical Responsementioning
confidence: 99%